Deep Ecology and Nature: Naess, Spinoza, Schelling - Meurs, Boris van (The Trumpeter, 2019)
In this article I will critically engage with Arne Naess's Deep Ecological appropriation of Spinoza's concept of Nature. I will argue that Naess falsely opposes the creative and created aspects of Nature, rather than thinking these two in concord. Because of this, his concept of Nature falls apart into two realms, which makes it impossible to think of Nature as one united whole. I will discuss the problems this leads to then propose that Schelling's philosophy of Nature is more apt as a Deep Ecological philosophy. Schelling's concept of Nature explicitly defines Nature as the identity of productivity and product, so that the rift in Naess's conception is overcome.